Evaluasi Pelaksanaan Program Bantuan Pangan Non Tunai (BPNT) Di Negeri Tawiri Kecamatan Teluk Ambon Kota Ambon - Lorena K. Siregar; H. V. R. Pattimukay; Jeanly Waisapy (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
This research is a descriptive qualitative study that aims to analyze the Evaluation of the Implementation of the Non-Cash Food Assistance Program in Tawiri Village, Teluk Ambon District. This research was conducted in Tawiri Village, Teluk Ambon Sub-district. Primary data were collected through interviews with a number of informants who were directly involved in the implementation of the Non-Cash Food Assistance Program in Tawiri Village, Teluk Ambon Sub-district. The results showed that the implementation of the Non-Cash Food Assistance Program in Tawiri Village, Teluk Ambon Sub-district went well despite the many obstacles encountered. This can be seen from 6 (six) policy evaluation criteria namely effectiveness, efficiency, adequacy, equity, responsiveness and accuracy where four of them have not been implemented optimally. So for the suggestions submitted, namely the need to submit the latest data or government officials must make updates related to Non-Cash Food Assistance for underprivileged people who do not get assistance and consult directly with village assistants, the Government as the organizer is obliged to provide socialization to Beneficiary Families about the Non-Cash Food Assistance Program, the Government also needs to improve administrative data on families who receive benefits.